Comparative Study of the Enforcement Guarantees of Literary and Artistic Property Rights in the Legal Systems of Afghanistan and Iran - Fazel Rabi Khairkhah; Saifuddin Jahed; Rahmatullah Fazil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Literary and artistic property rights are considered among the most important branches of intellectual property law, playing a fundamental role in supporting creativity, innovation, and cultural development. The infringement of these rights, in addition to causing financial and moral damages to creators, weakens scientific, literary, and artistic motivations within society. This study examines and analyzes the enforcement mechanisms for the infringement of literary and artistic property rights in Afghan law through a comparative study with Iranian law. In this research, the civil and criminal sanctions related to the infringement of the rights of authors, writers, artists, and researchers have been analyzed, along with the role of precautionary measures, compensation for damages, seizure and confiscation of unlawful works, prevention of continued infringement, publication of court judgments, and judicial prosecution. The type of this research is qualitative and the method employed for collecting data is based on documentary and library research. In other words, after examining the relevant texts, the findings have been described and analyzed on the basis of the principles governing literary and artistic property rights. The findings of the study indicate that both the Afghan and Iranian legal systems have provided relatively extensive mechanisms for the protection of literary and artistic property rights. Nevertheless, shortcomings remain in certain areas, including the precise determination of moral damages, the deterrent effect of punishments, and the effective implementation of laws. The study concludes that strengthening civil and criminal enforcement mechanisms, accelerating judicial proceedings, and achieving greater harmony with international standards can play a significant role in reducing violations of literary and artistic property rights and ensuring effective protection for creators.